PENGENDALIAN MODUL PROCESSING BEBASIS SEQUENTIAL FUNCTION CHART (SFC) - Suhendra Suhendra; Agus Halim; Soeharsono G (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: Automation is a technology that can be used to implement an instructional process or an automatic procedures. In this framework that has been using an instructional program that combined with a control system to process an instruction or commands. This processing module is a part of the automation engine which checking a process simulation of hollow and not hollow objects, then a PLC is to be needed to control all of the working processing modules systems which system works as you want. To control a working system, a programming language that easily to be understood is needed such as functional block diagram (FBD) which functional block diagram (FBD) is a method that can describe a function between input and output variable, in FBD there is a Sequential Function Chart method (SFC) which control the program sequential activity. So this research discusses the control of processing module which using FBD programming language by using the SFC method.